Morphological and Cultural Perspectives on Acronyms Through Sundanese Snack Names for BIPA Learning - Yeti Mulyati; Ananda Siti Khoirunnisa (Universitas Pendidikan Mandalika, 2026)
Acronyms in the Indonesian language function as tools for efficient communication and cultural expression. It's essential to introduce an acronym in Indonesian for Foreign Speakers (BIPA) learning to enhance learners’ understanding of language and culture. This study aims to describe the morphological patterns of acronyms in Sundanese snack names. It also examines their pedagogical relevance for BIPA learners. A qualitative descriptive method was used. The study analyzed a corpus of 39 acronyms of Sundanese snacks. Morphological approaches were applied to identify patterns of word formation. The analysis found that most acronyms are formed by combining nouns and incorporating active and passive verbs. The acronym word-formation includes the most common process of syllable merging. Specific acronyms use distinctive phonemes related to their ease of pronunciation. The acronym formation reflects both the linguistic structure and the cultural aspects of Sundanese society. These acronyms can enrich learners’ vocabulary and raise learners’ awareness of linguistic patterns. Moreover, using these acronyms in BIPA learning supports intercultural understanding. Integrating local cultural elements through acronyms provides authentic and meaningful learning experiences. It also contributes to Indonesia’s cultural diplomacy. This study highlights acronyms as both linguistic tools and cultural resources. Overall, these findings suggest practical insights for BIPA teachers in designing culturally responsive learning activities that integrate morphology, local culture, and contextual language use.